2004
DOI: 10.1177/1471301204042335
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Health

Abstract: Providing meaningful activities for persons with dementia in institutional care settings challenges many activity staff. Horticultural therapy (HT), is one approach to addressing this challenge. HT involves the use of plant materials to achieve measurable treatment goals with special populations. The current exploratory study investigated differential responses of persons with dementia to three types of HT activities: cooking, crafts, and planting. We conducted HT activities three times per week at an adult da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Spending time in nature is associated with good health outcomes, in particular when patients undertake activities such as gardening, which are useful for well-being and neuro-rehabilitation [52,53]. Some hospital are now equipped with healing gardens to stimulate the contact of patients with nature [54] and horticultural therapy has been found to be a successful activity to alleviate dementia [55]. Within this context, forests may be important not only for prevention but also for rehabilitation and stress relief.…”
Section: Discussionmentioning
confidence: 99%
“…Spending time in nature is associated with good health outcomes, in particular when patients undertake activities such as gardening, which are useful for well-being and neuro-rehabilitation [52,53]. Some hospital are now equipped with healing gardens to stimulate the contact of patients with nature [54] and horticultural therapy has been found to be a successful activity to alleviate dementia [55]. Within this context, forests may be important not only for prevention but also for rehabilitation and stress relief.…”
Section: Discussionmentioning
confidence: 99%
“…Horticultural therapy (HT) is a process through which gardening activities, interaction with plants and closeness to nature are used as a rehabilitative strategy (Simson and Straus, 1998). Horticultural therapy has been shown to improve mood state reducing stress and its contribution to coronary heart disease (based on POMS score) (Wichrowski et al, 2005), improve self-esteem and reduce depression (Son et al, 2004; Lee et al, 2008), improve sleep and cognitive issues in dementia patients (Lee and Kim, 2008), improve engagement and mood-related to dementia (Gigliotti et al, 2004; Gigliotti and Jarrott, 2005) and as a general treatment for mental health issues (Szofran and Myer, 2004). Further, horticultural activities (Richards and Kafami, 1999) and integrated adventure therapy programs (Bennett et al, 1998), have been shown to be useful in substance abuse treatment.…”
Section: Physical and Mental Health Disordersmentioning
confidence: 99%
“…All procedures were performed in accordance with the Helsinki Declaration. We estimated that a sample size of 15 would allow us to detect signi cant differences in the cognitive score before and after gardening activity with 80% power (α = 0.05) by previous studies (Alston, 2010) (Gigliotti, Jarrott, & Yorgason, 2004) and we determined our sample size to be 15.…”
Section: Methodsmentioning
confidence: 99%